The Influence of the Learning Together Type Cooperative Learning Model Assisted by Smart Closet Media on Students' Social Sciences Learning Outcomes - Rahamtillah*, Rahmatillah; Zulfan, Zulfan; Azis, Abdul (Universitas Syiah Kuala, 2024)
Smart cupboard media is one of the simple media, which contains knowledge in it which is able to teach students to dare to express opinions or knowledge that they have gained so that it can grow students' ideas and insights, which makes students more focused in learning and speed in thinking so that they can improve results. student learning. The problem in this research is the low value of students' social studies learning outcomes. This research aims to determine (1) the application of the cooperative learning model of joint learning type assisted by smart cupboard media on the social studies learning outcomes of class VIII students at SMPN 1 Bandar Baru. (2) find out how much influence the learning outcomes have before and after using the cooperative learning model of the joint learning type assisted by smart cupboard media on the social studies learning outcomes of class VIII students at SMPN 1 Bandar Baru. This research uses a quantitative approach with a pre-experimental design research type, in the form of a one group pretest-posttest design where there is only one group. The population in this study was all 6 class VIII students. The sample in this study was 32 students in class VIII.2 who were given treatment in the form of implementing a cooperative learning model using the smart cupboard media. The sampling technique uses a purposive sampling technique. The data collection techniques used are tests and documentation. The data analysis technique uses the normality test, homogeneity test, and t-test for the difference between two means. The results of this research were obtained from the scores before using the cooperative learning model with the help of smart cupboard media and the posttest with an instrument in the form of 15 multiple choice questions. Based on hypothesis testing using the t test (paired t test), the tcount = 8,389 and the ttable value at the = 0.05 level with df = 30 is 2,042, meaning tcount ttable or 8,389 2,042 at the Original Article Page 2 of 10 Rahmatillah et al. http://doi.org/10.24815/jimps.v9i1.xxxx significance level = 5% (0 .05) then Ho is rejected and Ha is accepted or there is a real (significant) influence of the variable on the variable of the cooperative learning model type of joint learning assisted by smart cupboard media on learning outcomes in class VIII-2. Based on this description, it proves that the use of the cooperative learning model of the joint learning type assisted by smart cupboard media has a very positive effect on student learning outcomes in social studies subjects in class VIII.2 at SMP Negeri 1 Bandar Baru.